Dual RNA-seq reveals transcriptome changes during Fusarium virguliforme-Trichoderma afroharzianum interactions. - Mirian F Pimentel; Leonardo F Rocha; Arjun Subedi; Jason P Bond; Ahmad M Fakhoury (PLoS ONE)
Trichoderma spp. are among the most studied biocontrol agents. While extensive work has been done to understand Trichoderma antagonistic mechanisms, additional research is needed to fully understand how Trichoderma spp. recognize the pathogen-host and the intra-species variability i frequently observed upon interaction with a specific pathogen-host. This study focuses on elucidating the mechanisms underlying observed phenotypic differences among the T. afroharzianum isolates Th19A and Th4 during confrontation with Fusarium virguliforme by investigating differences in their transcriptome at different stages of interaction. In a dual plate assay, Th19A overgrows F. virguliforme, whereas Th4 forms an inhibition zone. Significant differences were observed in the F. virguliforme transcriptome upon interaction with Th19A compared to Th4 and across the different stages of interaction. GO molecular function categories enriched for F. virguliforme genes differed, indicating possible transcriptional plasticity upon interaction with Th19A versus Th4. Significant transcriptome changes were also observed in T. afroharzianum, with several differences in GO-enriched categories between isolates. Several differentially expressed genes-encoding secreted proteins, including CAZymes and CBM1-domain-containing proteins, were up-regulated in Th19A and Th4 upon interaction with the pathogen, even before physical contact, demonstrating possible volatile-mediated recognition of both isolates by F. virguliforme. This study contributes to a better understanding of the interaction between T. afroharzianum and F. virguliforme, which is crucial for developing efficient biological control programs.